El Cucuy! : a bogeyman cuento in English and Spanish - Hayes, Joe.; Robledo, Honorio (El Paso, TX : Cinco Puntos Press, 2003)
A retelling of the story of two sisters who do not obey their father and are carried off into the mountains by el Cucuy.
Reprint. Originally published: 2001.
Parallel texts in English and Spanish.
Keywords: Folklore -- Mexico; Spanish language materials; Spanish language materials -- Bilingual; Folklore -- Mexico; Monsters -- Juvenile fiction; Spanish language materials -- Bilingual; Mexico -- Juvenile fiction